2009
DOI: 10.1088/0957-0233/20/4/045302
|View full text |Cite
|
Sign up to set email alerts
|

High resolution determination of radii of curvature using Fabry–Perot interferometry

Abstract: A spectroscopic approach to measuring the radius of curvature of a concave mirror is presented. The mirror is incorporated into a plano-concave Fabry–Perot cavity and the radius of curvature of the concave mirror is inferred from the mode spacing of the transverse modes relative to the longitudinal modes. No mechanical displacement is entailed and the measurement is easily performed in vacuum. The spectroscopic resolution of the technique is better than 1 µm for a nominal radius of curvature of 1 m, but the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The best approach to gain access to the Gouy phase is to make use of higher-order transverse modes of the cavity. This idea has been used to measure the radius of curvature of the curved mirror of a plano-concave cavity [21] with high precision; here, we interpret similar experiments in terms of the Gouy phase shift. Expanding the reflective phase shift uðmÞ to first order as…”
Section: Principle Of the Gouy Phase Measurementsupporting
confidence: 54%
“…The best approach to gain access to the Gouy phase is to make use of higher-order transverse modes of the cavity. This idea has been used to measure the radius of curvature of the curved mirror of a plano-concave cavity [21] with high precision; here, we interpret similar experiments in terms of the Gouy phase shift. Expanding the reflective phase shift uðmÞ to first order as…”
Section: Principle Of the Gouy Phase Measurementsupporting
confidence: 54%
“…Lawall et al incorporated concave mirror into plano-concave Fabry-Perot cavity to measure ROC by using the principle of multi-beam interference [4]. Sun et al demonstrated a differential radius-measuring system to perform high-precision ROC measurement through the interference-length measuring technology [5]. Wang et al proposed a differential confocal self-collimation decentration measurement method, which can obtain ROC of optical element by using the differential confocal to precisely identify the center and vertex positions of the tested lens surface [6].…”
Section: Introductionmentioning
confidence: 99%